‘Slobs and yobs’: representations of youth in the UK newspapers 1st January to 30th June 2005 - Robson, Elaine M. (2008)
Many authors have pointed to the ways in which newspapers negatively stereotype young people. This thesis aims to engage with and contribute to this debate through a contemporary discursive analysis of newspaper representations of youth, in The Guardian, The Daily Mail and The Daily Mirror during the period 1(^st) January to 30(^th) June 2005. My aim is to make explicit the discourses, both contemporary and historical, that circulated in the press during this period. It is through such discourses that young people were identified, explained and represented at this juncture. It will be argued that those young people deemed problematic by the press are represented in particular classed ways and understood through a discourse of 'underclass'; by which young people are constructed as victims of their families. Further, in 2005, as in the nineteenth- century, the poor working-class (understood as uncultured/uncivilized) are blamed for societies ills and such a discursive configuration has inevitable consequences and effects for both young people and their families